Acute LDL-C reduction post ACS: strike early and strike strong: from evidence to clinical practice. A clinical consensus statement of the Association for Acute CardioVascular Care (ACVC), in collaboration with the European Association of Preventive Cardiology (EAPC) and the European Society of Cardiology Working Group on Cardiovascular Pharmacotherapy. Issue 12 (27th December 2022) - Krychtiuk, Konstantin A; Ahrens, Ingo; Drexel, Heinz; Halvorsen, Sigrun; Hassager, Christian; Huber, Kurt; Kurpas, Donata; Niessner, Alexander; Schiele, Francois; Semb, Anne Grete; Sionis, Alessandro; Claeys, Marc J; et al.
Abstract: After experiencing an acute coronary syndrome (ACS), patients are at a high risk of suffering from recurrent ischaemic cardiovascular events, especially in the very early phase. Low density lipoprotein-cholesterol (LDL-C) is causally involved in atherosclerosis and a clear, monotonic relationship between pharmacologic LDL-C lowering and a reduction in cardiovascular events post-ACS has been shown, a concept termed 'the lower, the better'. Current ESC guidelines suggest an LDL-C guided, step-wise initiation and escalation of lipid-lowering therapy (LLT). Observational studies consistently show low rates of guideline-recommended LLT adaptions and concomitant low rates of LDL-C target goal achievement, leaving patients at residual risk, especially in the vulnerable post-ACS phase. In addition to the well-established 'the lower, the better' approach, a 'strike early and strike strong' approach in the early post-ACS phase with upfront initiation of a combined lipid-lowering approach using high-intensity statins and ezetimibe seems reasonable. We discuss the rationale, clinical trial evidence and experience for such an approach and highlight existing knowledge gaps. In addition, the concept of acute initiation of PCSK9 inhibition in the early phase is reviewed. Ultimately, we focus on hurdles and solutions to provide high-quality, evidence-based follow-up care in post-ACS patients.